TINJAUAN SADD AL-DZARĪ’AH TERHADAP PENETAPAN PERMOHONAN DISPENSASI KAWIN DI PENGADILANA AGAMA KEDIRI: Studi Penetapan Hakim Nomor 7/Pdt.P/2024/PA.Kab.Kdr - nur hidayati jannah, amirah; Al Amin, Habibi (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2024)
This research analyzes and discusses the determination of judge No. 7/Rev. P/2024/Pa.Kab.Kdr Sadd Al-Dharī'ah perspective. This research is liberal research or what is called library research. The data that has been collected is the judge's decision in case number 7/Pdt.P/2023/PA Kab. Kdr to be analyzed. The data collection method is carried out by observation and analysis of decisions. Data analysis uses descriptive analysis. This research concludes first, the legal considerations for determining the Judge of the Kediri Regency Religious Court No. 7/Pdt.P/2024/PA.Kab.Kdr is that the application for marriage dispensation is granted based on Article 12 paragraphs (1) and (2) PERMA Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Applications, Article 7 paragraph (2) of the Law. Law Number 1 of 1974 concerning Marriage which has been amended by Law Number 16 of 2019. Legal considerations by the Kediri Regency Religious Court Judge in determination No. 7/Pdt.P/2024/PA.Kab.Kdr sadd al-dharī'ah perspective is appropriate. This correspondence can be proven from wāṣīlah and ghāyah.